2021
DOI: 10.4314/as.v20i3.11
|View full text |Cite
|
Sign up to set email alerts
|

Bio-enhanced removal of hydrocarbon contents from spent engine oil contaminated soil using Staphylococcus aureus and Bacillus cereus co-culture

Abstract: The study assessed the removal of total petroleum hydrocarbon (TPH) and polyaromatic hydrocarbons (PAHs) from spent engine oil (SEO) contaminated soil through bioenhancement of bacteria isolated from SEO polluted soil. Sterilized soil was subjected to a three level of SEO contamination before the addition of sterilized biostimulants including powdered cow dung (CD), powdered cocoa pod husk (CPH) and compost (made from fresh CPH and CD). Bacterial inoculum being Staphylococcus aureus and Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
2
3
0
1
Order By: Relevance
“…The results obtained from this study show enhanced TPH degradation due to compost application to the SEO-contaminated soil. The TPH reduction orchestrated through the bio-stimulatory influence of compost in this study corroborates previous findings by Agbor et al (2012); Agbor et al (2015); Adeleye et al (2020); Adeleye et al (2021), with reference to its capacity for such achievement. This further corroborates the findings of Okoh (2006), who reported that organic wastes bind rapidly to the soil particle, and this facilitates the movement of the pollutants through the soil when natural events like rain occur.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results obtained from this study show enhanced TPH degradation due to compost application to the SEO-contaminated soil. The TPH reduction orchestrated through the bio-stimulatory influence of compost in this study corroborates previous findings by Agbor et al (2012); Agbor et al (2015); Adeleye et al (2020); Adeleye et al (2021), with reference to its capacity for such achievement. This further corroborates the findings of Okoh (2006), who reported that organic wastes bind rapidly to the soil particle, and this facilitates the movement of the pollutants through the soil when natural events like rain occur.…”
Section: Discussionsupporting
confidence: 93%
“…The addition of compost in this study resulted in enhanced TPH degradation in the SEO-contaminated soil. A similar result was also obtained by Adeleye et al (2021), where they observed a reduction in TPH and Polycyclic Aromatic Hydrocarbons (PAHs) content of SEO contaminated soil. The reduction in TPH content in this study could be due to the fact that mycorrhizal fungi notable active bio-fertilization interacted with some other beneficial soil organisms in order to achieve complete clean-up of polluted soils (Chibuike, 2013).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Spent engine oil (SEO) is typically referred to as used motor oil that has been collected from mechanical workshops, garages, and industrial sources such as hydraulic oil, turbine oils, process oil, and metalworking fluids (Olufemi and Oladeji, 2008). Disposal of SEO into gutters, watercourses, open vacant plots, and farmland are common practice among auto machine operators (Adeleye et al, 2020). This practice practically increases the incidence of oil pollution of agricultural soils and the built environment.…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de que los océanos no son afectados directamente por la eutrofización, debido a que las aguas profundas y frías, ricas en nutrientes, se encuentran por debajo de una capa establemente cálida, la cual constantemente pierde sustancias nutritivas, debido a que el plancton y el excremento del mismo se hunden (GIL et al, 2012;GONZÁLEZ CÁZAREZ et al, 2020). A través de la biorremediación, donde las cepas bacterianas, entre las que destacan las gram negativas, poseen características metabólicas que crecen en ambientes con altas concentraciones de metales o hidrocarburos (BHATNAGAR & KUMARI, 2013;ADELEYE et al, 2021), donde la relación intra e interpoblacional puede generar compuestos intermediarios que, a su vez, puede ser utilizado por otros microorganismos (NARVÁEZ FLÓREZ, GÓMEZ, Y MARTÍNEZ, 2008).…”
Section: Introduciónunclassified